Wellbeing and health psychology: the difficulty to measure quality of life - Sabrina Femenia; José-Félix Lozano (Quaderns de Psicología, 2019)
We present a conceptual overview around Wellbeing (WB) and some reflections about the necessity and difficulty of measure it. We start by analyzing the WB concept from the different axis, components, and dimensions (that form part of it. Also, we include and present different theories and conceptions that have been evolving through history, from Hedonism and Eudaimonic to modern psychological WB, Self-Determination Theory, Objective list, or Desires Theories to Authentic Happiness. Based on this revision, we are going to analyzing critically some of the most influential measure indicators of WB proposed during last two decades. Two are the main conclusions of our work: one is that indicators proposed lacks of integration of multiple WB dimensions that can offer a precise idea of the multidimensionality of the concept; second, an accurate, integrate and rigorous WB concept and measurement is an essential condition for effective and fair public policy.